PERANCANGAN SISTEM INFORMASI CATATAN DAN PENGAWASAN HEWAN TERNAK MENGGUNAKAN QR CODE BERBASIS WEB DENGAN METODE AGILE - Tubagus Fuady; Dadang Amirudin; Ahmad Surahmat; Ahmad Rifai (Jurnal Ilmiah Sains dan Teknologi, 2023)
Livestock as one of the mainstay sectors for development progress. The first role of animal husbandry is to produce high quality food ingredients such as: meat, milk and eggs which contain complete animal protein with essential amino acids. Second, livestock is also a source of income and employment opportunities for the community, in caring for it the community has a tradition of releasing buffalo, goats or sheep simultaneously in plantation areas, rice fields and even to the streets, this release makes it difficult for breeders to know which livestock belong to other breeders because livestock do not have markings, in recording mating data, administering vaccines, as well as the health condition of goats manually using a book. However, this will be very troublesome if the number of livestock being raised is very large, moreover the data that must be recorded is also complicated. With the existence of an Information System for livestock records and supervision using a web-based qr code with an agile method that utilizes the use of barcode technology. The data collection method used is interview, observation, literature study documentation. System development method created by Extreme Programming (XP). The Extreme Programming method is one of the most frequently used methodologies in Agile Development. With UML design. The purpose of designing this information system is that it is hoped that breeders can be assisted in recording and surveillance